Apolipoprotein E isotype-dependent modulation of microRNA-146a in plasma and brain. Issue 11 (3rd August 2016) - Teter, Bruce; LaDu, Mary Jo; Sullivan, Patrick M.; Frautschy, Sally A.; Cole, Greg M.
Abstract : The Apolipoprotein E (ApoE) isotype ApoE4 is a prevalent genetic risk factor for Alzheimer's disease (AD) that can modulate systemic and central inflammation, independent of amyloid accumulation. Although disruption of innate immune toll receptor signaling is modulated by ApoE and observed in AD, ApoE isotype-specific effects remain poorly understood. Therefore, we examined the effect of the ApoE isotype on the brain levels of major regulators of TLR signaling including miR146a, a microRNA enriched in the brain. We used 6-month-old ApoE3 or ApoE4 targeted replacement mice with and without mutant familial AD transgenes. ApoE4 reduced the levels of miR146a compared with ApoE3, both in the brain (29%; P <0.0001) and in plasma (47%; P <0.05), which correlated with each other ( r 2 =0.74; P <0.05). The presence of 5xFAD transgenes increased brain miR146a in both ApoE3 (E3FAD) and ApoE4 (E4FAD) mice; however, miR146a levels in E4FAD mice remained lower than those in E3FAD mice (62%; P <0.05), despite increased amyloid and inflammation. Supporting these observations, ApoE4 brains showed increased expression of interleukin receptor-associated kinase-1 (160%; P <0.05) (normally downregulated by miR146) that correlated inversely with miR146a levels ( r 2 =0.637; P <0.0001). Reduced negative feedback of toll-like receptor signaling (by miRNA146a) can explain early-life hypersensitivity to innate immune stimuli (including Aβ) in ApoE4 carriers. Thus, ApoE4 causes early dysregulation of a central controller of the innate immune system both centrally and systemically. This defect persists with familial AD pathology and may be relevant to ApoE4 AD risk.